Menelisik Nilai Sejarah dan Filosofi dalam Kebudayaan Melayu Langkat Melalui Tradisi Pernikahan dan Kue Rasidah - Rahmatain, Imam Baihaqi; Alhafizh, Rahmat; Dongoran, Mustofa; Siregar, Yusra Dewi (Medan Resource Center, 2023)
This study examines the historical and philosophical values embedded in the culture of the Malay Langkat, with a focus on wedding traditions and Rasidah cake. The wedding traditions in the Malay Langkat community not only reflect rich customs but also involve rituals filled with historical and philosophical significance. Rasidah cake, as an important element in ceremonial processes, holds deep meaning that reflects the personality and identity of the Malay community. This research employs a qualitative approach using in-depth interviews and literature studies to further explore the role of traditions and Rasidah cake in strengthening the cultural identity of the Malay Langkat. The findings indicate that wedding traditions and Rasidah cake serve not only as cultural symbols but also as a means of preserving ancestral values that continue to evolve within the Malay Langkat community to this day.